PENGARUH INTERAKSI NEGATIF TEMAN SEBAYA TERHADAP PERILAKU KONSUMTIF PADA SANTRI REMAJA PUTRI - Almas Azimatun Qonita; Anisa Agustanti (Jurnal Tawadhu, 2025)
Study this aim for know: exist influence between interaction Friend peer with behavior consumer . Population study This is student class XI SMA IT Ihsanul Fikri with totaling 340 students and the sample of this aim is class XI-10, totaling 32 students, was determined with technique purposive random sampling. Tool measure used is scale behavior consumptive And scale interaction Friend arranged peers according to method Likert Scale. Technique analysis hypothesis use technique analysis Product moment Hypothesis on study know influence interaction Friend peer with behavior consumer. Results hypothesis that is There is influence positive negative between interaction Friend peer with behavior consumptive, value correlation product moment 0.505 which means There is influence negative ones positive between interaction Friend peer to behavior consumer. The more high interaction Friend peer so the more high behavior consumerism, I see Also the more low interaction Friend peer so the more low behavior consumer. Results study This state that donation given effectiveness by interaction Friend peer And behavior consumption is 25.5% , meanwhile the remaining 74.5% is affected by other factors do not researched in study This like factor family And self concept.